2020
DOI: 10.1021/acs.orglett.0c01621
|View full text |Cite|
|
Sign up to set email alerts
|

Cation Radical-Accelerated Nucleophilic Aromatic Substitution for Amination of Alkoxyarenes

Abstract: Nucleophilic aromatic substitution (S N Ar) is a common method for arene functionalization; however, reactions of this type are typically limited to electron-deficient aromatic halides. Herein, we describe a mild, metal-free, cation-radical accelerated nucleophilic aromatic substitution (CRA-S N Ar) using a potent, highly oxidizing acridinium photoredox catalyst. Selective substitution of arene C−O bonds on a wide array of aryl ether substrates was shown with a variety of primary amine nucleophiles. Mechanisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…11 Of particular interest in this context is the work of Nicewicz, who showed that photoredox chemistry could be harnessed to effect nucleophilic aromatic substitution (SNAr) of nonactivated substrates. 12,13,14 The SNAr reaction typically requires activated substrates carrying electron-withdrawing groups (Figure 2b), but Nicewicz and coworkers showed that photooxidation of the substrate to the radical cation can increase its reactivity substantially. Here we show that similar reactivity can also be accessed without the use of a separate photoredox catalyst, by sequential photoabsorption of the substrate to access the radical cation intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…11 Of particular interest in this context is the work of Nicewicz, who showed that photoredox chemistry could be harnessed to effect nucleophilic aromatic substitution (SNAr) of nonactivated substrates. 12,13,14 The SNAr reaction typically requires activated substrates carrying electron-withdrawing groups (Figure 2b), but Nicewicz and coworkers showed that photooxidation of the substrate to the radical cation can increase its reactivity substantially. Here we show that similar reactivity can also be accessed without the use of a separate photoredox catalyst, by sequential photoabsorption of the substrate to access the radical cation intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…8 Further expansion of photocatalysed S N Ar of anisoles has been reported by the Nicewicz group. 9,10 We proposed that these conditions could be adapted to allow mild and efficient intramolecular reactions. The Smiles rearrangement is an intramolecular S N Ar reaction occurring at the ipso position in an aromatic system.…”
mentioning
confidence: 99%
“…Our publication at this stage is prompted by the very recent report from the Nicewicz lab which details the use of primary alkylamine nucleophiles in intermolecular radical-cation accelerated nucleophilic aromatic substitutions. 10 Our studies began with the evaluation of 2-phenoxyethan-1amine (6a). Pleasingly, the reaction of 6a (0.4 mmol) with 9-mesityl-3,6-di-tert-butyl-10-phenylacridinium tetrafluoroborate (PC1) (5 mol%) in a 1 : 1 mixture of 2,2,2-trifluoroethanol (TFE) and 1,2-dichloroethane (DCE) under visible light irradiation with a general purpose 40 W blue LED lamp (see ESI † for light source characterisation) in a nitrogen atmosphere for 24 hours at ambient temperature gave the rearranged product 7a in 87% solution yield ( Table 1, entry 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations